Implementation of the discovery learning model with engaged writing strategy and image media in improving fantasy story writing skil - Arti Prihatini; Ho Ngoc Hieu; Anfiya'ul Baroroh; Hidayah Budi Qur'ani (University of Muhammadiyah Malang, 2023)
Fantasy story writing requires imagination, reasoning, sensitive feelings, and self-motivation to discover and process narrative ideas. Thus, this study describes how the discovery learning model with engaged writing strategies and image media improves fantasy narrative writing. This research employed a Quasi-Experimental Design. Data was collected using writing tasks, tests, and semi-structured interviews. Data analysis was conducted using SPSS Statistics and Microsoft Excel software. The research sample was class VII students at SMP Muhammadiyah 15 Brondong, Lamongan Regency. Research shows that the discovery learning model with engaged writing strategies and picture media improves fantasy narrative writing skills by integrating students' thoughts, feelings, and intrinsic motivation. The findings were evident from the Mann-Whitney U test, which showed a significant influence of this innovative learning model with a post-test value (0.0000005) and writing task value (0.00000001). Selain itu, hasil N-Gain value kelas eksperimen lebih tinggi (71%) dibandingkan kelas kontrol (5.4851%). By integrating engaged writing and image media, the discovery learning model significantly enhanced the experimental group's capacity to compose fantasy stories. However, the expository model was less effective in the control group. Thus, discovery learning models with engaged writing strategy and image media may improve fantasy story writing ability.